E-cigarette use and perception among Malaysian: findings from text-mining analytics - Kartiwi, Mira; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Draman, Samsul; Ab Rahman, Norny Syafinaz (Malaysian Medical Association, 2017)
Introduction: E-cigarette use among adults are steadily increasing over the past few years. It is highlighted by the significant increases in online search queries and sharing of information through social media, such as Twitter. However, little attention has been given on understanding the reasons that led to e-cigarette use among Malaysian. In particular, study that leverage the opportunity to extract critical information from textual data in social media by using text mining technique. It is the aim of this paper to share the potential use of such technique by providing overview of processes and examples of the insights derived from the analysis. Methods: In this study, the textual analytics was used to identify topics and extract meanings from social media posts, in this case Twitter. The messages posted by Malaysian users from 2012 to early 2017 containing any of the selected keywords or phrase (i.e., #vape, #ecig, #vaping, #ejuice, #vapemalaysia) were collected using its search application programming interface (API). A total of 4211 messages containing original tweets were retrieved. Results: The result from the text mining analytics show that mainly there were three themes emerged on the reasons of e-cigarette use, namely: the sense of being part of a bigger community, e-cigarette is perceived more fun as compared to smoking conventional cigarette, and flavour of e-liquid. The result also shows that there was a spike on Twitter activity in 2015, where the topic on vape community were mostly posted. Discussion: The three themes identified in this study reveal initial reactions of public to Malaysian Government initiatives to regulate e-cigarette. It is believed that such findings would allow the government and medical practitioners to better understand public knowledge levels and identify current misunderstandings.